The efectiveness of the corporate governance in the corporations owned by the State: FONAFE and Petroperú cases - Gárate Salvatierra, Carlos Enrique (2022)
The article develops the concept of good corporate governance and how it has been incorporated into the regulations for companies and, especially, state-owned companies. In this way, the main factors that affect the effectiveness of good corporate governance practices in State companies are explained in comparison to the effectiveness that can occur in companies with purely private shareholders. For this analysis, the case of companies under the scope of FONAFE and Petroperú will be taken as a reference. Finally, proposals are made to improve the development of good corporate governance practices in state companies.